Walckenaeria stylifrons and Spiracme mongolica (Araneae, Linyphiidae, Thomisidae), two new species to Slovakia - Pavol Purgat (Pensoft Publishers, 2021)
The spiders Walckenaeria stylifrons (O. Pickard-Cambridge, 1875) and Spiracme mongolica (Schenkel, 1963) are reported from Slovakia for the first time. These new records are based on adult males found in Western Slovakia in xerothermic habitats. The occurrence of W. stylifrons in Slovakia fills the gap in its distribution in Pannonian Basin and between Austria and Ukraine. Spiracme mongolica has been known only from the Balkans and south-eastern part of Europe to central Asia, this is the first record for Central Europe. We suggest Spiracme mongolica (Schenkel, 1963) new combination for Xysticus mongolicus Schenkel, 1963. Characteristic features, photographs of habitus and copulatory organs, and habitats of the new records are presented.